Application of an adaptive line enhancer for HF/VHF data transmission - 334593 Mah, Chew Hon (Kuala Lumpur : UTM, 1994)
Basically, there are two ways in which informatioon can be transmitted over a transmission medium : analog or digital. During the course of data transmission, the signal is affected by two basic mechanisms i.e. the distortion effect on the signal due to non ideal transfer function of the transmission lines and the unwanted electrical noise or encironment effects. Consequently, the quality of the received signal will be degraded. This tesis concentrates mainly on the effectiveness of an adaptive line enhancer that will further improve the degraded signal. The processing technique used is baseed on an adaptive algorithm known as LMS (Least-Mean-Square). The characteristics of adaptive filter configuration which control the systtem performance will be identified. The research is focussed on the simulation of signal corrupted with additive noise in a bandpass digital data transmission system. The simulation results will be analyzed based on the improvement of signal-to noise ratio (SNR) and bit-error-rate (BER) performance.